Comprehensive review of renewable energy curtailment and avoidance: A specific example in China. (January 2015) - Li, Canbing; Shi, Haiqing; Cao, Yijia; Wang, Jianhui; Kuang, Yonghong; Tan, Yi; Wei, Jing
Abstract: Concerns over climate change (global warming) are driving innovation for stabilizing and reducing greenhouse gas (GHG) emissions. Technologies like carbon capture and storage (CCS) as well as renewable energy sources including wind and solar have been increasingly used and integrated into existing energy systems. The global installed renewable energy capacity booms, but many problems regarding grid integration appears due to the variability and uncertainty in the output of renewable energy generation. Therefore, large amount of curtailed electric energy (CEE) exists, which means some of the renewable energy generation must be wasted to keep real-time balance between load and generation in power system. In this paper, the definition of CEE is introduced, and the main causes for CEE are discussed. Then, the worldwide CEE is estimated, especially in China. Moreover, to evaluate the utilization priority of various generation resources, the potential of reducing fossil fuel consumption, GHG emissions and air pollutants as well as the potential of capturing CO2 with CEE are analyzed. Possible CEE reduction strategies are also presented.